Early-stage quality—late-stage confidence: Neural induction quality control as a key to reproducible MEA-based neurotoxicity assays - Ilka Scharkin; Jochen Dobner; Nadine Pierchala; Kristina Bartmann; Ulrike Hübenthal; Farina Bendt; Gabriele Brockerhoff; Andrea Rossi; Ellen Fritsche; Julia Tigges; Katharina Koch (NeuroToxicology, 2026)

Assessing the toxicity of traffic-derived air pollution using a primary human air-liquid interface airway in vitro model - Gerrit Bredeck; Tina Wahle; Angela A.M. Kämpfer; Jochen Dobner; A. John F. Boere; Paul Fokkens; Evert Duistermaat; Tim Spannbrucker; Andrea Rossi; Flemming R. Cassee; Roel P.F. Schins (Environmental Research, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Verbesserte humane induzierte pluripotente Stammzellen - Jochen Dobner (BIOspektrum, 2024)

Moderne Sequenzierungstechnologien und ihre Anwendungen - Jochen Dobner; Andrea Rossi (BIOspektrum, 2023)
CRISPR-mediated genome editing enables to study disease-relevant mutations. Next Generation Sequencing offers high throughput and accuracy but requires substantial investment. Nanopore sequencing on the other hand provides cheap entry. Here, we describe our work using sequencing techniques to identify edited cells, analyze mitochondrial DNA, and gene expression. Finally, we describe how our software tools CRISPRnano and Duesselpore aid to democratize the use of modern sequencing technologies.